Intellectualist Aristotelian Character Education: An Outline and Assessment. Issue 6 (December 2014) - Ferkany, Matt; Creed, Benjamin
Abstract Since its resurgence in the 1990s, character education has been subject to a bevy of common criticisms, including that it is didactic and crudely behaviorist; premised on a faulty trait psychology; victim‐blaming; culturally imperialist, racist, religious, or ideologically conservative; and many other horrible things besides. Matt Ferkany and Benjamin Creed examine an intellectualist Aristotelian form of character education that has gained popularity recently and find that it is largely not susceptible to such criticisms. In this form, character education is education for practically intelligent virtue, or the intrinsically motivated and psychically harmonious exercise of robust and stable traits involving practical intelligence conducive to individual and collective human flourishing.